Heterogeneous Antibody-Based Activity Assay for Lysine Specific Demethylase 1 (LSD1) on a Histone Peptide Substrate. (July 2014) - Schmitt, Martin L.; Ladwein, Kathrin I.; Carlino, Luca; Schulz-Fincke, Johannes; Willmann, Dominica; Metzger, Eric; Schilcher, Pierre; Imhof , Axel; Schüle, Roland; Sippl, Wolfgang; Jung, Manfred
Posttranslational modifications of histone tails are very important for epigenetic gene regulation. The lysine-specific demethylase LSD1 (KDM1A/AOF2) demethylates in vitro predominantly mono- and dimethylated lysine 4 on histone 3 (H3K4) and is a promising target for drug discovery. We report a heterogeneous antibody-based assay, using dissociation-enhanced lanthanide fluorescent immunoassay (DELFIA) for the detection of LSD1 activity. We used a biotinylated histone 3 peptide (amino acids 1–21) with monomethylated lysine 4 (H3K4me) as the substrate for the detection of LSD1 activity with antibody-mediated quantitation of the demethylated product. We have successfully used the assay to measure the potency of reference inhibitors. The advantage of the heterogeneous format is shown with cumarin-based LSD1 inhibitor candidates that we have identified using virtual screening. They had shown good potency in an established LSD1 screening assay. The new heterogeneous assay identified them as false positives, which was verified using mass spectrometry.